denovo-db: a compendium of human de novo variants. - Turner, Tychele N; Yi, Qian; Krumm, Niklas; Huddleston, John; Hoekzema, Kendra; F Stessman, Holly A; Doebley, Anna-Lisa; Bernier, Raphael A; Nickerson, Deborah A; Eichler, Evan E (Nucleic Acids Res, 2017)
Whole-exome and whole-genome sequencing have facilitated the large-scale discovery of de novo variants in human disease. To date, most de novo discovery through next-generation sequencing focused on congenital heart disease and neurodevelopmental disorders (NDDs). Currently, de novo variants are one of the most significant risk factors for NDDs with a substantial overlap of genes involved in more than one NDD. To facilitate better usage of published data, provide standardization of annotation, and improve accessibility, we created denovo-db (http://denovo-db.gs.washington.edu), a database for human de novo variants. As of July 2016, denovo-db contained 40 different studies and 32,991 de novo variants from 23,098 trios. Database features include basic variant information (chromosome location, change, type); detailed annotation at the transcript and protein levels; severity scores; frequency; validation status; and, most importantly, the phenotype of the individual with the variant. We included a feature on our browsable website to download any query result, including a downloadable file of the full database with additional variant details. denovo-db provides necessary information for researchers to compare their data to other individuals with the same phenotype and also to controls allowing for a better understanding of the biology of de novo variants and their contribution to disease.
Keywords: Computational Biology; Databases, Nucleic Acid; Genetic Association Studies; Genetic Variation; Germ-Line Mutation; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Web Browser